PENGARUH PERENDAMAN PARTIKEL TERHADAP SIFAT FISIS DAN MEKANIS PAPAN PARTIKEL DARI AMPAS TEBU (Saccharum officinarum) - Apri Heri Iswanto; Zahrial Coto; Kurniawansyah Effendy (PERENNIAL, 2008)
The objective of this research is to research the effect of particle soaking to physical and mechanical properties particleboard that resulted. The best result of particleboard is particleboard with treatment of hot water soaking. From this result obtained average of physical properties of particleboard (i.e. density, moisture content, water absorption, and thickness swelling) are 0.7 g/cm3; 9.58%; 52.27%; 10.05%. While the result average of mechanical properties of particleboard (i.e. Modulus of Rupture, Modulus of Elasticity, Internal Bond and Screw Holding Power) are 118.79 kg/cm2; 8.909 kg/cm2; 1.85 kg/cm2; 28.40 kg. Key words: Soaking, bagasse, particleboard, physical and mechanical properties References